Melihat Olahraga Nasional dari Sudut Pandang Kepemimpinan: Sebuah Pengantar - Joko Purnomo (Institut Pemerintahan Dalam Negeri (IPDN), 2016)
This paper aims to acknowledge and describe Indonesia sports phenomenon from leadership point of view. With using qualitative approach and qualitative method also literature study as a frame, authors try to describe sports phenomenon in Indonesia which is gained from other sources linked with author conceptual idea itself namely the absent of Indonesia Sports Leadership and it solution; Self Leadership; Transformative Leadership and; Sports Leadership Pyramid Model. Paper result is Sport Leadership Pyramid Model is a new breakthrough of Indonesia Sports Leadership problems. It has special process starts from self leadership until leader character. They should be able to adopt transformative leadership in each process.